2015
DOI: 10.4236/aim.2015.58062
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of <i>Staphylococcus warneri</i> in the Hair of ICU Doctors

Abstract: This study reports a case of Staphylococcus warneri dissemination in the hair of ICU/ER doctors. Eleven of 23 doctors in the first survey and 11 of 24 doctors in the second survey, which were conducted after 6 months, carried S. warneri, while hair contamination of other coagulase-negative staphylococci was only sporadic. Chromosomal DNA analysis with PFGE revealed that 7 S. warneri strains isolated in the first survey and 7 strains isolated in the second survey showed similar PFGE patterns, suggesting that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…The observation of a PFGE type with several representatives demonstrates the circulation of a single clone in the hospital and community. Previous studies have shown a higher diversity of S. warneri [ 40 ] and the dissemination of a single clone among health professionals [ 41 ]. The paucity of molecular epidemiology studies involving S. warneri hinders understanding the clonality of this species.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of a PFGE type with several representatives demonstrates the circulation of a single clone in the hospital and community. Previous studies have shown a higher diversity of S. warneri [ 40 ] and the dissemination of a single clone among health professionals [ 41 ]. The paucity of molecular epidemiology studies involving S. warneri hinders understanding the clonality of this species.…”
Section: Discussionmentioning
confidence: 99%
“…The indiscriminate use of these antibiotics has led to an increase in the occurrence of multidrug-resistant Staphylococcus. It was described for S. warneri, genes that can confer resistance to non-beta-lactam antibiotics, such as fluroquinolones and glycopeptides (vancomycin and teicoplanin) [10,14,15].…”
Section: Resultsmentioning
confidence: 99%
“…Os Estafilococos coagulase negativos fazem parte da microbiota residente das mãos e, embora sejam bem resistentes à remoção mecânica ou agentes químicos e não eliminados mesmo com uma higienização adequada, não oferecem riscos aos indivíduos saudáveis. Porém, podem causar infecções em pessoas imunologicamente comprometidas (SANTOS, 2002;SHAMOTO et al, 2015).…”
Section: Figura 1 Momentos Em Que Os Manipuladores De Uma Unidade Deunclassified